2009
DOI: 10.1097/sap.0b013e31818938bb
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome After Pedicled Segmental Pectoralis Major Island Flaps for Head and Neck Reconstruction

Abstract: The pectoralis major is reliable for reconstruction of large defects in the head and neck area. In 2001, we introduced a muscle-sparing technique with preservation of the clavicular part of the muscle. So far, we did not report on its reliability and clinical outcome at the receptor site.Fifty-four pedicled segmental pectoralis major island flaps were used in 53 patients, from 2001 through 2006. As outcome measures, we studied the overall rate of complications, the rate of major complications, and the final ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Corten et al [13] and McLean et al [15] also reported that there was a significant correlation between a past history of radiotherapy and overall complications. In addition, Pinto et al [14] reported that there was a significant correlation between hypopharyngeal reconstruction and overall complications.…”
Section: Discussionmentioning
confidence: 99%
“…Corten et al [13] and McLean et al [15] also reported that there was a significant correlation between a past history of radiotherapy and overall complications. In addition, Pinto et al [14] reported that there was a significant correlation between hypopharyngeal reconstruction and overall complications.…”
Section: Discussionmentioning
confidence: 99%
“…According to documented literature reports by Kiyokawa et al [17] as well as others [6,20,22,23], the use of pectoralis major myocutaneous pedicled flap has solved two important problems, the first problem is postoperative infection caused by foreign body reactions or movement between the plate and the surrounding tissue and the second problem is metal plate exposure caused by pressure applied to the skin overlying the mandible, gingiva, or grafted skin flap which can be best addressed by completely rolling the muscular tissue of the pectoralis major myocutaneous flap around the metal plate. When compared with skin or subcutaneous tissue, muscular tissue facilitates wound healing to a greater degree [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with skin or subcutaneous tissue, muscular tissue facilitates wound healing to a greater degree [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the PMMPF has been widely used in head and neck reconstruction since its first introduction by Ariyan in 1979 [1][2][3][4], many studies have revealed the reliability of free tissue transfer since the 1980s. Therefore, the role of the PMMPF in head and neck reconstruction has been supplanted by free tissue transfer in several situations [3,4,9].…”
Section: Discussionmentioning
confidence: 99%
“…The pectoralis major myocutaneous pedicled flap (PMMPF) is considered the "workhorse" flap for head and neck reconstruction operations after its introduction in 1979 by Ariyan [1][2][3][4]. Despite advancements in microsurgery, this flap continues to be the primary reconstructive choice for several reasons, such as good coverage, readily identifiable and reliable bloody supply, reduced operative time, simple technical aspects, lower patient comorbidity, and proximity to the head and neck region [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%